Obesity in male volcano mice Neotomodon alstoni affects the daily rhythm of metabolism and thermoregulation - Herrera-García, Andrea; Pérez-Mendoza, Moisés; Arellanes-Licea, Elvira del Carmen; Gasca-Martínez, Deisy; Carmona-Castro, Agustín; Díaz-Muñoz, Mauricio; Miranda-Anaya, Manuel (Frontiers in Nutrition, 2022)
The mouse N. alstoni spontaneously develops the condition of obesity in captivity when fed regular chow. We aim to study the differences in metabolic performance and thermoregulation between adult lean and obese male mice. The experimental approach included indirect calorimetry using metabolic cages for VO2 intake and VCO2 production. In contrast, the body temperature was measured and analyzed using intraperitoneal data loggers. It was correlated with the relative presence of UCP1 protein and its gene expression from interscapular adipose tissue (iBAT). We also explored in this tissue the relative presence of Tyrosine Hydroxylase (TH) protein, the rate-limiting enzyme for catecholamine biosynthesis present in iBAT. Results indicate that obese mice show a daily rhythm persists in estimated parameters but with differences in amplitude and profile. Obese mice presented lower body temperature, and a low caloric expenditure, together with lower VO2 intake and VCO2 than lean mice. Also, obese mice present reduced a thermoregulatory response after a cold pulse. Results are correlated with a low relative presence of TH and UCP1 protein. However, qPCR analysis of UCP1 presents an increase in gene expression in iBAT. Histology showed a reduced amount of brown adipocytes in BAT. The aforementioned indicates that the daily rhythm in aerobic metabolism, thermoregulation, and body temperature control have reduced amplitude in obese mice Neotomodon alstoni.